Diurnal Fluctuations of Verticality Perception – Lesser Precision Immediately after Waking up in the Morning - Schwarz, Aline J.; Straumann, Dominik; Tarnutzer, Alexander A. (Frontiers in Neurology, 2015)
Internal estimates of direction of gravity are continuously updated by integrating vestibular, visual and proprioceptive input and prior experience about upright position. Prolonged static roll-tilt biases perceived direction of gravity by adaptation of peripheral sensors and central structures. We hypothesized that in the morning after sleep estimates of direction of gravity (assessed by the subjective visual vertical (SVV)) are less precise than in the evening because of adaptation to horizontal body position and lack of prior knowledge about upright position. Using a mobile SVV-measuring device, verticality perception was assessed in seven healthy human subjects on seven days in the morning immediately after waking-up and in the evening while sitting upright. Paired t-tests were applied to analyze diurnal changes in SVV trial-to-trial variability. Average SVV variability in the morning was significantly larger than in the evening (1.9±0.6° vs. 0.9±0.3°, p=0.002). SVV accuracy was not significantly different (-1.2±0.9° vs. -0.4±0.4°, morning vs. evening, p=0.058) and was within normal range (±2.3°) in all but one subject. A good night’s sleep has a profound effect on the brain’s ability to estimate direction of gravity. Resulting variability was significantly worse after waking-up reaching values more than twice as large as in the evening while there was no significant impact on SVV accuracy. We hypothesize that lacking prior knowledge, adaptation of peripheral sensors and lower levels of arousal and cerebral metabolism contribute to such impoverished estimates. Our observations have considerable clinical impact as they indicate an increased risk for falls and fall-related injuries in the morning.